Assessing Mathematical Connections Abilities in Algebraic Operations: A Qualitative Case Study of Eight-Grade Students - Drajat, Widi Rahmawati; Jupri, Al (FKIP Universitas Lampung, 2025)
With a case study approach, this qualitative research aims to determine students' mathematical connection ability in solving mathematical problems with algebraic arithmetic operations. The subjects of this study were 30 students of grade VIII at a junior high school in Indramayu Regency. The data collection technique in this study used several instruments, namely mathematical connection ability test questions, interviews, and documentation. The data analysis technique used a descriptive method consisting of three main stages: data reduction, data presentation, and conclusion. Based on the analysis of the entire question instrument, it was found that most students had difficulty solving problems by linking relationships between topics in mathematics. In addition, students are not yet able to think about using mathematical concepts in other fields of study and have not been able to apply mathematical concepts widely in everyday life. This low mathematical connection ability can be caused by several factors, including students' lack of conceptual understanding, learning methods that have not optimized the relationship between topics in mathematics, and the lack of contextual and applicable practice questions. This indicates that the learning provided still tends to focus on procedures without emphasizing the relationship between concepts in more depth. More innovative learning strategies are needed to improve students' mathematical connection skills, such as problem-based learning, contextual learning, and integrating mathematical concepts with real life and other fields of study. Thus, the level of mathematical connection abilities of grade VIII students is still relatively low, so efforts are needed to improve learning strategies to develop mathematical thinking skills more broadly and connect with various contexts. Keywords: algebraic operation, mathematical connection ability, mathematical problems.